Development of venous thromboembolism (VTE) in patients undergoing surgery for brain tumors: Results from a single center over a 10 year period. Issue 3 (March 2015) - Smith, Timothy R.; Nanney, Allan D.; Lall, Rishi R.; Graham, Randall B.; McClendon, Jamal; Lall, Rohan R.; Adel, Joseph G.; Zakarija, Anaadriana; Cote, David J.; Chandler, James P.
Abstract Patients who undergo craniotomy for brain neoplasms have a high risk of developing venous thromboembolism (VTE), including deep vein thromboses (DVT) and pulmonary emboli (PE). The reasons for this correlation are not fully understood. This retrospective, single-center review aimed to determine the risk factors for VTE in patients who underwent neurosurgical resection of brain tumors at Northwestern University from 1999 to 2010. Our cohort included 1148 patients, 158 (13.7%) of whom were diagnosed with DVT and 38 (3.3%) of whom were diagnosed with PE. A variety of clinical factors were studied to determine predictors of VTE, including sex, ethnicity, medical co-morbidities, surgical positioning, length of hospital stay, tumor location, and tumor histology. Use of post-operative anticoagulants and hemorrhagic complications were also investigated. A prior history of VTE was found to be highly predictive of post-operative DVT (odds ratio [OR] = 7.6, p = 0.01), as was the patient's sex (OR = 14.2, p < 0.001), ethnicity (OR = 0.5, p = 0.04), post-operative intensive care unit days (OR = 0.2, p = 0.003), and tumor histology (OR = −0.16, p = 0.01). Contrary to reports in the literature, the data collected did not indicate that the administration of post-operative medical prophylaxis for VTE was significant in preventing their formation (OR = −0.14, p = 0.76). Hemorrhagic complications were low (2.2%) and resultant neurologic deficit was lower still (0.7%). The study indicates that patients with high-grade primary brain tumors and metastatic lesions should receive aggressive preventative measures in the post-operative period.